Thermophysical properties of the pure ionic liquid 1-butyl-1-methylpyrrolidinium dicyanamide and its binary mixtures with alcohols - Gonçalves, JC (2013)
Experimental density, speed of sound, viscosity, and refractive index data for the pure ionic liquid 1-butyl-1-methylpyrrolidinium dicyanamide, [BMpyr][dca], are reported from T = (293.15 to 343.15) K, together with the molar isobaric heat capacity from T = (293.15 to 333.15) K. Moreover, a thermal analysis was carried out for the pure ionic liquid using a differential scanning calorimetry. The density, speed of sound, refractive index, and molar isobaric heat capacity data were fitted to a simple polynomial (first and/or second order), while viscosity data were fitted to the Vogel-Fulcher-Tamman (VFT) equation. From the experimental density values, the thermal expansion coeffi cient was also calculated. For the binary systems {1-propanol, or 2-propanol, or 1-butanol + [BMpyr][dca]}, density, speed of sound, and refractive index data were also measured over the whole composition range at T = (298.15, 313.15 and 328.15) K and p = 0.1 MPa. From these data, the excess molar volumes and excess molar isentropic compressions were calculated and satisfactorily fitted to the Redlich-Kister equation. Finally, the obtained results are discussed in terms of interactions and structure factors in these binary mixtures. (c) 2013 American Chemical Society.